SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN MENGGUNAKAN METODE SAW (Simple Additive Weighting) - kurnialensya; yuli fitrianto (STEKOM PRESS, 2020)
Arzara company is a company engaged in the garment sector, the development of the company affects the level of production of goods, so that in order to balance the production needs, it must increase the number of employee needs. The problem that often occurs in Arzara's company is the lack of professionalism of the company's employees, resulting in unilateral termination of employment. Termination of employment of employees of course will also affect the amount of production of goods. The SAW method or often called Simple Additive Weighting is an algorithmic method used for decision making, using certain criteria as the weight of the assessment in decision support. In making employee admission decisions using the SAW method using several criteria, which include expertise (skills), work experience, age, gender, education, health, talent, character, temperament, character, general knowledge tests, psychological tests. By using the PHP programming language, it can be used to assist the company to perform valid recruitment of employees . Applications that have been made can be used as a tool for decision makers while remaining based on a decision support system that is more effective in selecting employee admissions using the SAW ( Simple Additive Weighting ) method .